Epigenetic Inheritance of Paternally Expressed Imprinted Genes in the Testes of ICSI Mice - Xu, Xiang-Rong; Fu, Rong-guo; Wang, Li-Ya; Wang, Ning; Zhang, Fan; Le, Fang; Li, Lei; Li, Le-Jun; Liu, Xiao-Zhen; Zheng, Ying-Ming; Lou, Hang-Ying; Jiang, Shi-Wen; et al. (Current Pharmaceutical Design, 2014)
Worse reproductive health in the men born through intracytoplasmic sperm injection (ICSI) or other assisted reproductive techniques (ART) has been reported in many studies. However, owing to the interference of genetic and environmental factors, it is difficult to identify whether ICSI method would affect male reproductive health. Therefore, ART mouse models were established in this study. Besides semen quality, serum testosterone and histological analysis of testes, 6 paternally expressed imprinted genes were chosen to detect their expressions and methylation levels in testes of adult F1 and F2 mice. Although the phenotypic abnormalities weren’t found, Kcnq1ot1, Mest, Peg3, Plagl1 and Snrpn in ICSI group showed lower expressions than those in naturally conceived (NC) group. The expressions of Kcnq1ot1, Peg3 and Snrpn in in vitro fertilization (IVF) conceived mice was lower than those in controlled ovarian hyperstimulation (COH) conceived mice, but higher than those in ICSI mice. Most differences between NC and ICSI group and between IVF and ICSI group were also represented in F2 generations. During the methylation analysis, no matter there was significant difference between compared groups, the changing trends of methylation level were almost opposite to their corresponding gene expressions. These results indicated that the differential expressions of paternally expressed genes occurred in testes of ICSI mice, which may be mediated by methylation modification. Both ICSI procedure and mechanical stimulation can induce intergenerational transmission of the epigenetic changes. In vitro culture and mechanical stimulation were the main factors inducing the down regulation of paternally expressed imprinted genes in testes.
Keywords: testis